LRH‐1/NR5A2 interacts with the glucocorticoid receptor to regulate glucocorticoid resistance. (8th July 2022) - Michalek, Svenja; Goj, Thomas; Plazzo, Anna Pia; Marovca, Blerim; Bornhauser, Beat; Brunner, Thomas
Abstract: Nuclear receptors are transcription factors with important functions in a variety of physiological and pathological processes. Targeting glucocorticoid receptor (GR) activity using glucocorticoids is a cornerstone in the treatment of patients with T cell acute lymphoblastic leukemia (T‐ALL), and resistance to GC‐induced cell death is associated with poor outcome and a high risk for relapse. Next to ligand‐binding, heterodimerization with other transcription factors presents an important mechanism for the regulation of GR activity. Here, we describe a GC‐induced direct association of the Liver Receptor Homolog‐1 (LRH‐1) with the GR in the nucleus, which results in reciprocal inhibition of transcriptional activity. Pharmacological and molecular interference with LRH‐1 impairs proliferation and survival in T‐ALL and causes a profound sensitization to GC‐induced cell death, even in GC‐resistant T‐ALL. Our data illustrate that direct interaction between GR and LRH‐1 critically regulates glucocorticoid sensitivity in T‐ALL opening up new perspectives for developing innovative therapeutic approaches to treat GC‐resistant T‐ALL. Synopsis: Physical interaction of liver receptor homolog‐1 (LRH‐1) with the glucocorticoid receptor contributes to glucocorticoid (GC) resistance. Treatment with the LRH‐1 inhibitor 3d2 reverses resistance, thereby re‐sensitizing leukemic T cells towards GC‐induced apoptosis. LRH‐1 inhibits the glucocorticoid receptor (GR) and regulates GC responsiveness of leukemic T cells. The LRH‐1 inhibitor 3d2 promotes GR induction and upregulation of the pro‐apoptotic BCL‐2 homolog Bim. Combined treatment of primary patient‐derived T‐ALL cells with GCs and LRH‐1 inhibitor results in synergistic cell death. LRH‐1 is a critical regulator of T‐ALL cell proliferation and survival. Abstract : Physical interaction of liver receptor homolog‐1 (LRH‐1) with the glucocorticoid receptor contributes to glucocorticoid (GC) resistance. Treatment with the LRH‐1 inhibitor 3d2 reverses resistance, thereby re‐sensitizing leukemic T cells towards GC‐induced apoptosis.